Outcome of Lateral Condyle Fracture of Humerus in Children Treated with Open Reduction and Internal Fixation - K.C., Dipendra; Mishra, S.M.; Yogi, Sushil; Shrestha, Dinesh; Karki, Prateek; Shrestha, Sabin (Journal of Nepalgunj Medical College, 2019)
Introduction: Lateral condyle fracture is one of the commonest injuries encountered in pediatric age group. There is no unanimity regarding the method of treatment, however closed reduction is not applicable to all cases and have failure rates making open reduction and internal fixation (ORIF) as the treatment of choice at least in displaced fractures. There are a number of options during surgical management of these fractures; Kirschner-wire (K-wire) is the most commonly used implant for fixation. The purpose of our study was to evaluate the results of lateral condyle fractures of humerus in children treated by ORIF by K-wires based on Hardacre criteria. Materials: This prospective study was conducted in the department of orthopedics in Nepalgunj Medical College Teaching Hospital, Kohalpur from May 2016 to October 2018. All of the fractures in this study were treated by ORIF with unburied K-wires. It included 37 children of age group upto 14 years. Children were evaluated for age, sex, side of arm involved, mechanism of injury, type of fracture, presence of additional injuries, implant removal time, outcome and accompanying complications. K-wires were removed after clinico-radiological union of the fractures. Patients were evaluated using the Hardacre criteria in follow up till 6 months. Result: In this study of 37 children, 28 (75.7%) were males and 9 (24.3%) were females. All of them were 14 years of age or less with mean age of 6.7 ± 0.316. Majority of fractures (67.6%) were observed between six to ten years of age. Left side was predominantly involved (62.2%). Milch type I fracture was found in 5 (13.5%) children while Milch type II fracture were observed in 32 (86.5%) children. The final outcome and functions were evaluated using Hardacre criteria in which 27 (73%) cases had excellent result and all cases had good result as per Hardacre criteria. The complications were 10 (27%) cases of lateral spur; eight (21.6%) cases of hypertrophied scar and four (10.8%) cases of pin track infection and 2 (5.4%) of cubitus varus. Conclusion: The treatment of displaced lateral condyle fracture of humerus by open reduction and unburied K-wire fixation is safe, easy and cost effective procedure with good results. This modality of treatment provides good results among pediatric population without the need for second admission for implant removal.